Effect of hot cracking on the mechanical properties of Hastelloy X superalloy fabricated by laser powder bed fusion additive manufacturing. (April 2020) - Han, Quanquan; Gu, Yuchen; Soe, Shwe; Lacan, Franck; Setchi, Rossitza
Highlights: Microcracks eliminated by reducing the minor alloying elements. The peak compressive strength increased with increasing strut sizes. The failure of with-cracking lattice structures is controlled by plastic buckling. Abstract: Nickel-based superalloys such as Hastelloy X (HX) are widely used in gas turbine engine applications and the aerospace industry. HX is susceptible to hot cracking, however, when processed using additive manufacturing technologies such as laser powder bed fusion (LPBF). This paper studies the effects of minor alloying elements on microcrack formation and the influences of hot cracking on the mechanical performance of LPBF-fabricated HX components, with an emphasis on the failure mechanism of the lattice structures. The experimental results demonstrate that a reduction in the amount of minor alloying elements used in the alloy results in the elimination of hot cracking in the LPBF-fabricated HX; however, this modification degrades the tensile strength by around 140 MPa. The microcracks were found to have formed uniformly at the high-angle grain boundaries, indicating that the cracks were intergranular, which is associated with Mo-rich carbide segregation. The study also shows that the plastic-collapse strength tends to increase with increasing strut sizes (i.e. relative density) in both the 'with cracking' and 'cracking-free' HX lattice structures, but the cracking-free HX exhibit a higher strength value. Under compression, the cracking-free HX lattice structures' failure mechanism is controlled by plastic yielding, while the failure of the with-cracking HX is dominated by plastic buckling due to the microcracks formed within the LPBF process. The novelty of this work is its systematic examination of hot cracking on the compressive performance of LPBF-fabricated lattice structures. The findings will have significant implications for the design of new cracking-free superalloys, particularly for high-temperature applications.